Strategic supply risk: exploring the risks deriving from a buying firm being of low importance for its suppliers. (2017) - Reichenbachs, Mauricio; Schiele, Holger; Hoffmann, Petra
This paper merges two important concepts: preferred customer and supply risk. As not all customers are of the same strategic importance to a supplier, some customers are treated preferentially. Strategic supply risk describes the risk for buyers of not being a preferred customer. This qualitative study explores the concept of strategic supply risk, its sources, indicators and mitigation tactics as well as its connection to social exchange theory. The findings suggest that strategic supply risk is likely to be present when among others the buyer accounts for a minor portion of supplier turnover. One important strategic supply risk indicator seems to be changes in the supplier's attitude toward the buyer. Aligning strategies, for example, can be a useful tactic for reducing strategic supply risk, whereas finding alternative sources of supply supports the mitigation of a buyer's strategic supply risk. The research enhances supply risk management research and adds a risk component to the literature on customer attractiveness and preferred customers. Additionally, this research presents initial guidelines for managers on how to set up an effective strategic supply risk management system.